Implementation of Educational Supervision in High Schools: Analysis of Academic Supervision Types, Techniques, and Processes - Neng Nurhayati; Neneng Aminah; Supardi; Agus Gunawan (JIEMAN: Journal of Islamic Educational Management, 2025)
Educational supervision plays a strategic role in improving instructional quality and strengthening teacher professionalism in senior high schools. However, supervision practices in many secondary education institutions remain ineffective due to the fragmented application of supervision types, inappropriate supervisory techniques, and poorly structured supervision processes. This study aims to systematically examine the implementation of educational supervision in senior high schools by analysing the interrelated dimensions of supervision types, supervision techniques, supervisory approaches, and academic supervision processes. The study employs a descriptive qualitative research design using a systematic literature review method to synthesise theoretical and empirical studies on educational supervision published between 2021 and 2025. Data were collected by documenting peer-reviewed journal articles, scholarly books, and research reports in Indonesian and English, and analysed using thematic descriptive analysis. The findings reveal that educational supervision in senior high schools is implemented through three integrated types: academic, managerial, and clinical supervision. Academic supervision focuses on improving teaching and learning processes through lesson planning review, classroom observation, and reflective dialogue. Managerial supervision strengthens school governance, leadership, and organisational effectiveness, while clinical supervision supports individualised teacher development through intensive and reflective feedback cycles. In addition, effective supervision is supported by the strategic combination of individual and group supervision techniques, as well as the adaptive use of directive, collaborative, and non-directive supervisory approaches based on teachers’ professional characteristics. The supervision process operates through a systematic cycle of planning, implementation, evaluation, and follow-up, ensuring sustainability and continuous instructional improvement.